A visegrádi országok felsőoktatásának jellemzői - Keczer, Gabriella (Közép-Európai Közlemények, 2014)
The so called „Visegrád” countries are Hungary, Poland, Slovakia and the Czech Republic. They have the same historic heritage and a similar path since the change of the political-economic system in 1990. We present, analyze and compare the higher education systems of the four countries. We examine the institutions, the governance, the input (new entrants), output (people with higher education attainment), the conditions (expenditure, student/teacher rate) of their higher education systems, and the value of the diplomas (graduate unemployment rate, salary). Our research is based on the most recent available statistical data of Eurostat and of the OECD, and on databases like Eurypedia and Eurydice.